Tracing the 'just' in just transition: conceptualizations of justice by citizens' juries in climate policy-making - Kulha, Katariina (Elsevier, 2026)
The efforts to mitigate climate change have been accompanied by calls for a just transition, meaning a sustainability transition that takes into account the social costs of policy change. While several studies have addressed the social justice impacts of climate policies, the desired implications of just transition remain contested, and the concept is constantly shaped by different actors involved in the policy-making of sustainability transition. In recent years, randomly selected citizen bodies, called deliberative mini-publics, have been convened to address issues of justice and to advance the acceptability of climate policies through the inclusion of citizens’ diverse viewpoints. However, relative to their increasing use in climate policy-making, mini-publics’ definitions of just climate policies have received little attention. The paper argues that mini-publics’ policy recommendations can enrich just transition scholarship’s understanding of the contestations revolving around justice in transitions. It therefore sets out to analyze the statements of three citizens’ juries discussing climate change mitigation policies in Finland. Based on an analytical frame drawn from the literatures of energy, environmental, and climate justice, the paper deconstructs the conceptualizations of justice present in the juries’ outputs. The results show that especially support for low-income groups and the acknowledgement of regional diversity are deemed important by the juries, who expect active measures from public authorities to safeguard both citizens’ well-being and environmental values. The findings suggest that advancing just transition requires policy mixes, where mitigation measures are explicitly combined with redistributive policies and investments in infrastructure and public services.